Massive Retropharyngeal Hematoma with Airway Obstruction after Minor Injury - Sobti, Shivender; Grewal, Sarvpreet Singh; John, Paul S.; Grover, Ashwani (Indian Journal of Neurotrauma, 2017)
Retropharyngeal hematoma can cause life-threatening airway compromise. We present a case of massive retropharyngeal hematoma following minor injury. The patient required immediate tracheostomy followed by evacuation of hematoma and cervical stabilization.
Keywords: retropharyngeal; hematoma; airway; obstruction